2019
DOI: 10.2196/11756
|View full text |Cite
|
Sign up to set email alerts
|

Understanding User Experience: Exploring Participants’ Messages With a Web-Based Behavioral Health Intervention for Adolescents With Chronic Pain

Abstract: Background Delivery of behavioral health interventions on the internet offers many benefits, including accessibility, cost-effectiveness, convenience, and anonymity. In recent years, an increased number of internet interventions have been developed, targeting a range of conditions and behaviors, including depression, pain, anxiety, sleep disturbance, and eating disorders. Human support (coaching) is a common component of internet interventions that is intended to boost engagement; however, little … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…A study of an internet-delivered pain management intervention for adolescents with chronic pain [90] used text mining and analytic techniques to messages between coaches and patients and successfully identified messages that raised concerns. Cluster analysis identified subgroups of individuals with common communication and engagement patterns that could be used to tailor interventions.…”
Section: Renderxmentioning
confidence: 99%
“…A study of an internet-delivered pain management intervention for adolescents with chronic pain [90] used text mining and analytic techniques to messages between coaches and patients and successfully identified messages that raised concerns. Cluster analysis identified subgroups of individuals with common communication and engagement patterns that could be used to tailor interventions.…”
Section: Renderxmentioning
confidence: 99%
“…Schäfer et al [ 60 ] identified “Web-based discussion topics associated with Gastrointestinal discomfort and its perceived factors in Web-based messages posted by users of French social media (p. 1)” using topic modeling to provide real-world evidence for caregivers. Chen et al [ 61 ] employed topic modeling and visual analytics techniques to characterize textual content generated during Internet behavioral health interventions. In [ 62 ], an RNN-based semi-supervised learning algorithm exploited rich unlabeled Web corpus.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of algorithm and method innovations, future efforts include: (1) using knowledge graphs to analyze medical information strongly relevant to expert knowledge to boost prediction performance [ 86 ], (2) adopting ontology-based methods to perform complex plan-oriented counseling and communication tasks [ 84 ], (3) utilizing CNNs and LSTM-CNN with diverse embedding and optimization technologies for epidemic outbreak analysis [ 44 ], (4) applying semi-automatic approaches to promote personalized healthcare information provided to facilitate users’ daily activities of living [ 76 ], (5) integrating additional security technologies like hashing to avoid malicious attackers [ 57 ], (6) using a combination of algorithms such as genetic algorithms and SVMs to facilitate accurate feature selection [ 55 ], and (7) adding more privacy-preserving statistics and machine learning algorithms to extensively promote flexibility in secure multicenters [ 57 ]. Additionally, there are scholars indicating the need to: (1) propose visual approaches to explore “the dyadic interaction between coaches and participants to better understand how to provide support and guidance to participants (p. 14) [ 61 ]”, and (2) analyze, mine, and extract Web page content by adopting machine learning algorithms and through quality information visualization within search engines [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall findings indicated a high level of efficacy. Several secondary analyses of the data from the main Web‐MAP2 trial have been conducted (Chen et al., 2019; Law et al., 2018; Murray et al., 2019).…”
Section: Resultsmentioning
confidence: 99%